Question
upstudy study bank question image url

Solve for \( y \). \( 4+\frac{1}{y+1}=\frac{5}{y+4} \) If there is more than one solution, separate them with commas, If there is no solution, dick on "No solution". \( y=\square \)

Ask by Paul Pierce. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( y = -2.5, -1.5 \)

Solution

Solve the equation \( 4+\frac{1}{y+1}=\frac{5}{y+4} \). Solve the equation by following steps: - step0: Solve for \(y\): \(4+\frac{1}{y+1}=\frac{5}{y+4}\) - step1: Find the domain: \(4+\frac{1}{y+1}=\frac{5}{y+4},y \in \left(-\infty,-4\right)\cup \left(-4,-1\right)\cup \left(-1,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(4+\frac{1}{y+1}\right)\left(y+1\right)\left(y+4\right)=\frac{5}{y+4}\times \left(y+1\right)\left(y+4\right)\) - step3: Simplify the equation: \(4y^{2}+21y+20=5y+5\) - step4: Move the expression to the left side: \(4y^{2}+21y+20-\left(5y+5\right)=0\) - step5: Calculate: \(4y^{2}+16y+15=0\) - step6: Factor the expression: \(\left(2y+3\right)\left(2y+5\right)=0\) - step7: Separate into possible cases: \(\begin{align}&2y+3=0\\&2y+5=0\end{align}\) - step8: Solve the equation: \(\begin{align}&y=-\frac{3}{2}\\&y=-\frac{5}{2}\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&y=-\frac{3}{2}\\&y=-\frac{5}{2}\end{align},y \in \left(-\infty,-4\right)\cup \left(-4,-1\right)\cup \left(-1,+\infty\right)\) - step10: Find the intersection: \(\begin{align}&y=-\frac{3}{2}\\&y=-\frac{5}{2}\end{align}\) - step11: Rewrite: \(y_{1}=-\frac{5}{2},y_{2}=-\frac{3}{2}\) The solutions to the equation \(4+\frac{1}{y+1}=\frac{5}{y+4}\) are \(y=-\frac{5}{2}\) and \(y=-\frac{3}{2}\). Therefore, the solutions are \(y=-2.5\) and \(y=-1.5\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( 4+\frac{1}{y+1}=\frac{5}{y+4} \), we first eliminate the fractions by multiplying both sides by \( (y+1)(y+4) \): \[ 4(y+1)(y+4) + 1(y+4) = 5(y+1) \] Expanding this gives: \[ 4(y^2 + 5y + 4) + (y + 4) = 5y + 5 \] Putting it all together: \[ 4y^2 + 20y + 16 + y + 4 = 5y + 5 \] Now simplify: \[ 4y^2 + 21y + 20 = 5y + 5 \] Rearranging yields: \[ 4y^2 + 16y + 15 = 0 \] Next, we can factor or apply the quadratic formula. This factors neatly to: \[ (4y + 3)(y + 5) = 0 \] Setting each factor equal to zero gives us: \[ 4y + 3 = 0 \quad \Rightarrow \quad y = -\frac{3}{4} \] \[ y + 5 = 0 \quad \Rightarrow \quad y = -5 \] Thus, the solutions are: \[ y = -\frac{3}{4}, -5 \] Final answer: \( y = -\frac{3}{4}, -5 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy